KONTROL DIRI DALAM PERSPEKTIF ISLAM DAN UPAYA PENINGKATANNYA MELALUI LAYANAN BIMBINGAN KONSELING ISLAM - Mansyur, S; Casmini, Casmini (At-Taujih : Bimbingan dan Konseling Islam, 2022)
This study seeks to provide a conceptual framework about self-control in an Islamic perspective and efforts to improve it through Islamic counseling and guidance services. This research is library research with descriptive type, the data collection is taken from various books and journals related to the theme and discussion. The results showed that self-control in Islam is a person's ability to direct his attitude and behavior based on faith and piety to Allah SWT. Efforts that can be made in increasing self-control are to provide Islamic counseling guidance services through individual counseling services using a Sufistic approach (takhalli, tahalli, and tajalli).
Keywords: Self Control; Islamic Counseling Guidance Service